2021
DOI: 10.3389/fphar.2021.640603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic and Non-genetic Predictors of Levodopa Induced Dyskinesia in Parkinson’s Disease

Abstract: Background: Levodopa (L-Dopa), representing the therapeutic gold standard for the treatment of Parkinson disease (PD), is associated with side effects like L-Dopa induced dyskinesia (LID). Although several non-genetic and genetic factors have been investigated for association with LID risk, contrasting results were reported and its genetic basis remain largely unexplored.Methods: In an Italian PD cohort (N = 460), we first performed stepwise multivariable Cox Proportional Hazard regressions modeling LID risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Albeit some studies found contradictory results on the association between the GBA1 and LRRK2 variants and LID, [39][40][41][42] many others have shown that these variants play a role in LID development, [27][28][29][30][31][32] and in this study we also demonstrated that LRRK2 variants might also affect the and disease-related factors. [9][10][11][12][13] The significant association between the two PRS analyses suggests that aggregating multiple common variants that might have a scarce effect on LID individually could contribute to uncovering the overall genetic impact on LID.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Albeit some studies found contradictory results on the association between the GBA1 and LRRK2 variants and LID, [39][40][41][42] many others have shown that these variants play a role in LID development, [27][28][29][30][31][32] and in this study we also demonstrated that LRRK2 variants might also affect the and disease-related factors. [9][10][11][12][13] The significant association between the two PRS analyses suggests that aggregating multiple common variants that might have a scarce effect on LID individually could contribute to uncovering the overall genetic impact on LID.…”
Section: Discussionsupporting
confidence: 56%
“…38 However, the association between LID and most of the abovementioned putative genetic risk factors is still controversial, with most findings reported deriving from candidate genes studies that failed to be confirmed in replication studies. [39][40][41][42][43][44] Here, we aimed to systematically evaluate how genetics affect the risk and rate of progression to LID including a total of 4,787 PD patients from multiple centers. For this purpose, we performed genome-wide association studies (GWAS) and downstream analyses focused on specific genes previously implicated in LID.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were of European ancestry and were evaluated by qualified neurologist of the Parkinson Centre from June 2015 to December 2017, with a thorough protocol comprising neurological examination and evaluation of non-motor domains. Information about family history, demographic characteristics, anamnesis, and pharmacological therapy was also collected [ 8 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parkinson's disease (PD) is characterized by the loss of dopaminergic neurons in the brain's substantia nigra (SN); proper treatment employs synthetic molecules 1 . These molecules are neuroprotective but can cause psychosis and hallucinations by creating a large number of reactive oxygen species that disrupt mitochondrial activity 2 . As a polygenic disease, PD involves several genes in its development; modifying the function of a single protein largely activates various pathways, which has synergistic effects on the disease process.…”
Section: Introductionmentioning
confidence: 99%